National Commissions of Inquiry in Africa: Vehicles to pursue accountability for violations of the right to life? - Thomas Probert (Pretoria University Law Press (PULP), 2020)
National commissions of inquiry in the aftermath of violations of human rights, including violations of the right to life, are a common feature of the African legal and political landscape. There is often a fair measure of scepticism or caution about their use, and with good reason. They can serve as convenient instruments to avoid accountability, rather than to achieve it. However, very little hard evidence is available upon which the performance of such commissions can be assessed, and hence impressions of their utility are often largely anecdotal. For the purposes of this book, researchers went to six countries in Africa-Chad, Burkina Faso, Kenya, Malawi, South Africa and Nigeria-and conducted in-depth investigations of commissions of inquiry that have been held there, interviewing those directly involved in the proceedings and those working on the issues since, including victims, lawyers, investigators and Commissioners. Drawing on this research, the book argues that commissions of inquiry should not be contrasted with courts or with criminal trials, since their proper place is at a different stage of the investigative process. Rather than replacing criminal processes, commissions might guide whether and how they should take place. Commissions can be cathartic events for victims or families; they can demonstrate that human rights are a priority for the state and thus lay the foundations for the rule of law; and they can make broader recommendations about what should be done. In short, in certain circumstances, they can serve to enable a broader concept of accountability. Praise for this publication "A rich collection of well-researched chapters made up of normative analysis and case studies, which presents a much-needed scholarly contribution to the question of accountability for violations of human rights-particularly the right to life-through a means other than a routine criminal process, a question with which the African Commission on Human and Peoples' Rights wrestled in its Study on Transitional Justice that was the basis for the African Union Transitional Justice Policy. The insights it offers on why, how and when Commissions of Inquiry in Africa facilitate accountability are profoundly informative not only for scholars but also for policy makers and practitioners." Solomon Ayele Dersso Chairperson, African Commission on Human and Peoples' Rights "This book covers new ground, with six rich case studies drawing from on-the ground research across the African continent. It demonstrates that while independent mechanisms can all face significant challenges in the aftermath of grave violations of human rights, properly-mandated, adequately-empowered and well-supported commissions of inquiry can in some cases play a valuable role within broader processes of accountability. The authors rightly focus on the complementarity of the different elements that a transitional justice process must have in order to be compatible with human rights standards, making an extraordinary theoretical contribution to debates about how to guarantee human rights in the face of atrocious facts." Fabián Salvioli UN Special Rapporteur on the promotion of truth, justice, reparation and guarantees of non-recurrence Table of Contents Background and acknowledgments & Members of the research team Introduction: The role of national commissions of inquiry in securing the supreme human right Thomas Probert & Christof Heyns A brief introduction to the right to life and the normative framework mandating accountability, including the duty to investigate potentially unlawful deaths, as well as to the broader research project lying behind this volume The concept of accountability and its importance for the protection of the right to life Thomas Probert A chapter that looks at how the mutually-reinforcing character of human rights accountability is fundamental to its definition, and the consequence that human rights accountability must contain three key elements: finding out what happened and who was responsible (investigations); finding waysof remedying the situation (remedies); and finding ways of preventing it from happening again (reforms). 'Lawfare', instruments of governmentality and accountability, or both? An overview of national commissions of inquiry in Africa Meetali Jain A chapter illustrating how commissions of inquiry have a long pedigree in the legal and bureaucratic architecture of several of the colonial powers in Africa, and have been adopted by many African governments during the post-colonial period. It explores how the commission of inquiry, as an instrument of governmentality, can be and has been imposed for the purpose of legalistic domination, but how it has sometimes acquired a life of its own and also catalysed reform. Commissions of inquiry and social solidarity in the African context Christof Heyns A chapter that discusses the extent to which it is possible to draw lessons from an historical emphasis on social solidarity to inform our understanding of the role of commissions in Africa. In particular, it explores the extent to which South African jurisprudence has been informed by or has deployed the concept of ubuntu and its impact on accountability, also for right to life violations Shedding all the light? The Commission of Inquiry into the Crimes and Misappropriations of Hissène Habré in Chad The first case-study chapter, this examines the Commission of Inquiry into the Crimes and Misappropriations Committed by Ex-President Habré, his Accomplices and/or Accessories, which took place in Chad in 1990 to 1991. Established by new President Idriss Déby after Habré had fled the country, it provided a rather one-sided account of the abuses that had occurred during the latter's rule. Nonetheless, its role in documenting violations, and its status as an official record adopted by the government of Chad, would go on to play a central role in the long story of the pursuit of justice for Habré's victims, culminating in the Extraordinary African Chambers verdict and his conviction in 2016. A murdered journalist and a crisis of faith in the judiciary: The Independent Commission of Inquiry into the Death of Norbert Zongo in Burkina Faso Thomas Probert Whereas that Chadian Commission reviewed evidence of violations that took place over eight years, and reported on thousands of deaths, the next case study, that of the Independent Commission of Inquiry into the Death of Norbert Zongo and His Four Companions in Burkina Faso in 1999, investigated the events of a single afternoon. This chapter shows how, while the Commission focused on the murder of a journalist, the mobilisation for its establishment, and the challenges it faced reflected a complete lack of faith of the official judicial machinery of Blaise Compaoré's regime. Public hearings and secret envelopes: The Waki Commission as a case study of accountability in Kenya Anyango Yvonne Oyieke The third case study is of the well-known Commission of Inquiry into Post-Election Violence in Kenya (sometimes called the Waki Commission). This Commission played a central role at the beginning of a long process of the pursuit of accountability for the abuses at the hands of both non-state and state actors in the aftermath of the 2007 election in Kenya. The Commission formed part of an internationally-mediated peace agreement, involved two international commissioners, and would ultimately end up implicated in a far more international process of indictments before the ICC that would lead to a sitting President appearing (briefly) in the dock at The Hague. A slow but steady search for justice: The Commission of Inquiry into the July 2011 'riots' in Malawi John Kotsopoulos The conduct of the police was also examined by the Commission of Inquiry into the Death and Destruction of Property during the events of July 2011 in Malawi. This case was an interesting example of a commission of inquiry investigating a single set of events (the state's response to a coordinated set of public protests across several cities) from multiple social perspectives, while also drawing important lessons for how the police ought to conduct public order operations.